Evolution illuminated : salmon and their relatives - Hendry, A. P. (Andrew P.); Stearns, S. C. (Stephen C.), 1946- (Oxford University Press, 2004)
This book will appeal to investigators in each of the scientific disciplines it integrates-evolutionary biology, ecology, salmonid biology, management, and conservation. Variation in salmonids can be used to illustrate virtually all evolutionary questions, and so the work will also attract general scientific interest by ecologists and evolutionary and conservation biologists.